Effects of step width and gait speed on the variability of mediolateral control in the head and trunk during gait - Yu Takada; Tomoaki Atomi; Takayuki Yagi; Shoma Yamamoto; Masao Tomita; Miho Shimizu; Yoriko Atomi (PLoS ONE, 2025)
Step width is a parameter that determines the size of the base of support (BOS) during gait. Further, it is related to the control of center of mass (COM) and trunk movements and gait speed. The current study aimed to validate the effect of conditioning using combined step width (narrow and wide) and gait speed (normal [4.5 km/h] and slow [2.2 km/h]) on the segmental control of the head, thorax, and pelvis with respect to the BOS. The behavior of the head, thorax, and pelvis of 17 healthy adult participants were measured during treadmill walking using a three-dimensional motion analysis system. If the step width was narrow, the whole body segment with a high contribution to COM under narrow BOS conditions was more likely to have a high variability. However, the mediolateral direction behavior was small. On the contrary, if the step width was wide, the whole body segment with a high contribution to COM under wide BOS conditions was more likely to have a low variability. Nevertheless, the mediolateral direction behavior was large. Regarding the intersegmental association, particularly if the step width was narrow and the gait speed was normal, the head showed highly controlled movements with minimal displacement and increased fine-tuning. The thorax displayed significant importance in maintaining trunk stability, operating within a larger range of mediolateral displacement compared to the head and pelvis, under three conditions, except if the step width was narrow and the gait speed was normal. The study underscores the significant impact of both step width and gait speed on the control and stability of high-mass body segments during gait. It suggests that narrow step widths necessitate advanced control strategies, while wide step widths promote simpler, compensatory mechanisms, especially relevant in clinical contexts.